Alternative Bone Graft Sources and Techniques for Tibiofibular Synostosis Creation Following Transtibial Amputation: A Report of Two Cases. Issue 1 (January 2015) - Overmann, Archie; Potter, Benjamin K.
Abstract : Case: Alternative methods of the modified Ertl osteomyoplasty with use of two different tibial grafts for synostosis are presented in two patients who underwent revision transtibial amputation. Conclusion: These two techniques spare residual limb length relative to other described local techniques, avoid the morbidity of remote autograft harvest, and may be attempted in patients with inadequate residual limb lengths or in those who have tibiofibular length mismatch to achieve stable bridge synostosis.